The upper limit of physiologic cardiac hypertrophy in highly trained elite athletes - Pelliccia, A.; Maron, B. J.; Spataro, A.; Proschan, M. A.; Spirito, P. (New England Journal of Medicine, 1991)
BACKGROUND. In some highly trained athletes, the thickness of the left ventricular wall may increase as a consequence of exercise training and resemble that found in cardiac diseases associated with left ventricular hypertrophy, such as hypertrophic cardiomyopathy. In these athletes, the differential diagnosis between physiologic and pathologic hypertrophy may be difficult. METHODS. To address this issue, we measured left ventricular dimensions with echocardiography in 947 elite, highly trained athletes who participated in a wide variety of sports. RESULTS. The thickest left ventricular wall among the athletes measured 16 mm. Wall thicknesses within a range compatible with the diagnosis of hypertrophic cardiomyopathy (greater than or equal to 13 mm) were identified in only 16 of the 947 athletes (1.7 percent); 15 were rowers or canoeists, and 1 was a cyclist. Therefore, the wall was greater than or equal to 13 mm thick in 7 percent of 219 rowers, canoeists, and cyclists but in none of 728 participants in 22 other sports. All athletes with walls greater than or equal to 13 mm thick also had enlarged left ventricular end-diastolic cavities (dimensions, 55 to 63 mm). CONCLUSIONS. On the basis of these data, a left-ventricular-wall thickness of greater than or equal to 13 mm is very uncommon in highly trained athletes, virtually confined to athletes training in rowing sports, and associated with an enlarged left ventricular cavity. In addition, the upper limit to which the thickness of the left ventricular wall may be increased by athletic training appears to be 16 mm. Therefore, athletes with a wall thickness of more than 16 mm and a nondilated left ventricular cavity are likely to have primary forms of pathologic hypertrophy, such as hypertrophic cardiomyopathy.